The Secrets of Chocolate : A GOURMAND'S TRIP THROUGH A TOP CHEF'S ATELIER - Alarcon, Franckie, 1974-; Kane, Montana (New York : NBM, 2021)
"Following Jacques Genin for a year, Franckie Alarcon hobnobbed with one of the biggest chefs of Chocolate. Former chef and pastry chef for prestigious restaurants, this super-talented autodidact shares all his passion and knowledge of chocolate and his process for creating recipes. In this docu-comic, we travel with the starry-eyed author, satisfying many a craving from the chef's amazing atelier above his store, trying his hand as an apprentice, all the way to the Peruvian cocoa plantations where another chef shows how one carefully chooses the beans."--Provided by publisher
Keywords: Chocolate -- Comic books, strips, etc